EMPIRICAL ANALYSIS OF DETERMINANT FACTORS IN IMPROVING THE JOB PERFORMANCE OF ENGLISH TEACHERS IN JUNIOR HIGH SCHOOLS IN INDONESIA - Reni Apriani; Nurul Afiyattena; Dede Engkos (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
The purpose of the research is to obtain information regarding the possibility of whether job performance is affected by the work environment, competence, and work satisfaction. Using a causal study through a survey of English teachers at junior high schools in Malingping District, Lebak Banten, Indonesia. The population of the study is 80 and the sample of this study consists of 46 teachers. The data for each variable were collected separately by the respondents who filled out the questionnaire. The method used in this study is a quantitative survey method, while the analytical technique used is regression analysis. The results prove that there is an effect of the work environment on performance, there is an effect of competence on performance, there is an effect of job satisfaction on performance, and there is an influence of work environment, competence, and work satisfaction on the sat performance of junior high school English teachers in Malingping District. These findings indicate that the strength of the work environment is driven by qualified workforce competence that brings work satisfaction to English Teachers, which partially shows the influence of these three variables on work performance